Developing a Cloud-Native Internship Management Platform: Enhanced Efficiency and Integration through Object-Oriented Architecture - Setiaji, Pratomo; Adiyono, Soni; Prayogo, Adhie; Kurniasari, Nita (Universitas Bina Darma, 2025)
The Internship Program Fieldwork Practice plays a crucial role in bridging academic learning and industry experience. However, traditional internship management faces challenges such as inefficient supervision, inconsistent attendance tracking, and lack of standardized performance evaluations. This study proposes a cloud-native internship management platform utilizing Object-Oriented Design (OOD) to enhance efficiency and accuracy in administrative processes. Developed using the Rapid Application Development (RAD) methodology, the system provides real-time monitoring, automated attendance tracking, and centralized performance assessment. User acceptance testing involving 35 participants, including students, lecturers, and industry supervisors, revealed significant improvements in administrative efficiency, student engagement, and data security. The platform ensures scalability, role-based access control, and secure data encryption. Findings highlight the need for standardized, technology-driven internship management solutions. Future research should explore AI-driven analytics and machine learning for optimizing internship experiences.